Housing Tenure and Housing Demand in Colombia - Maria Angelica Arbelaez; Roberto Steiner; Alejandro Becerra; Daniel Wills (Inter-American Development Bank (IDB), 2011)
Using the 2003 and 2008 Quality of Life Surveys, this paper identifies the factors that affect housing tenure decisions in Colombia. Households with higher incomes are more likely to purchase than to rent, and the choice of formal housing is positively associated with wealth. Households eligible for social housing subsidies are more likely to purchase than to rent, and those working in the informal sector are more likely to purchase informal dwellings. Subsidies and access to mortgage credit have a large positive impact on demand. Finally, savings have a positive effect on demand in 2008, but not in 2003. The positive effect on demand of both subsidies and credit is explained by demand for low- income housing.
Keywords: G21; O54; R21; R28; R38; R58; 330